FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU BULLYING DI SMA NEGERI 2 BANGKINANG KOTA TAHUN 2021 - PUTRI EKA SUDIARTI; MARINI ARIESTA; NURCHOLISAH FITRA (Universitas Pahlawan Tuanku Tambusai, 2021)
Bullying occurs when there is repeated abuse of power or power by one student who attacks because of an imbalance of power between the parties involved. The factors that cause bullying behavior include self-control and family parenting. The purpose of this study was to find out what are the factors associated with bullying behavior in students at SMA Negeri 2 Bangkinang Kota. This study is a quantitative study with a cross-sectional design. The population in this study is the number of students at SMAN 2 Bangkinang City in class X and class XI. The sample in this study were some students who were in SMA Negeri 2 Bangkinang Kota, totaling 101 people. The sampling technique in this study used a simple random sampling technique. The research was conducted in July 2021. The tool used in this study was a questionnaire. The questionnaire contains closed questions, namely questionnaires presented in a form such as Google Form. Data processing using chi-square test. The results of the study found that there was a significant relationship between self-control p value = 0.000 and family parenting p value = 0.002 on bullying behavior in students at SMA Negeri 2 Bangkinang City. Researchers expect that in associating students further improve self-control so that with self-control students are able to regulate their behavior to avoid deviant behavior.